(untitled) (Research, Society and Development, 2020)
In the last years, the relevance of sterilization and antisepsis processes has been widely discussed among healthcare professionals, including dental surgeons. However, in dental practice, the quality of the water used in the equipments, apparently harmless, can be considered a risk factor for the patient’s health. Therefore, the objective of this study was to verify the presence of contamination in dental equipments and to evaluate the water quality of the equipment’s reservoirs, through microbiological analysis. 12 water samples were collected directly from dental chair reservoirs and 12 samples from the triple syringe of six multidisciplinary clinics in the Department of Dentistry of the Federal University of Rio Grande do Norte (UFRN). Plating was performed using the Spread Plate method, on BHI agar medium (Brain Heart Infusion) with subsequent incubation in a bacteriological oven programmed at 37,5°C to 38°C, for a period of 24 to 48 hours. The results demonstrated that 83% of the incubated plates showed significant growth of filamentous fungi and bacteria that, due to the odor of tutti-fruti and based on macroscopic characteristics, are suggested to be of the genus Pseudomonas. In this context, the findings of this study attest to the urgency of developing a health care routine, enabling the decontamination of the equipment’s water systems as well as its reservoirs, meeting patient safety requirements, which must be inherent in dental offices.